2021
DOI: 10.21873/anticanres.15119
|View full text |Cite
|
Sign up to set email alerts
|

FosL1 Regulates Regional Metastasis of Head and Neck Squamous Cell Carcinoma by Promoting Cell Migration, Invasion, and Proliferation

Abstract: Background/Aim: We evaluated the impact of FosL1, a member of the activated protein-1 family, on the pathways leading to regional metastasis of head and neck squamous cell carcinoma (HNSCC). Materials and Methods: We examined the influence of small interfering RNA (siRNA) and short heparin RNA (shRNA) mediated knockdown of FosL1 on cell migration, invasion, and proliferation in vitro as well as on regional metastasis in vivo. The prognostic significance of FosL1 was also analyzed using the Kaplan-Meier plotter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Through transcriptional sequencing analysis, we found that the gene expression of FOSL1 and RAB5B was significantly increased after PMPs were added to two HCC cell lines. FosL1 plays a crucial role in promoting cell migration, invasion, and proliferation in neck squamous cell carcinoma, 39 and knockdown of RAB5B also inhibits cell proliferation, migration, and invasion in human breast cancer stem cell-like cells. 40 Under the intervention of PMPs, the changes of relevant proliferation genes also confirmed the fact that the tumor volume increased in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Through transcriptional sequencing analysis, we found that the gene expression of FOSL1 and RAB5B was significantly increased after PMPs were added to two HCC cell lines. FosL1 plays a crucial role in promoting cell migration, invasion, and proliferation in neck squamous cell carcinoma, 39 and knockdown of RAB5B also inhibits cell proliferation, migration, and invasion in human breast cancer stem cell-like cells. 40 Under the intervention of PMPs, the changes of relevant proliferation genes also confirmed the fact that the tumor volume increased in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…FOS1 also has prognostic value in various epithelial tumors, and its overexpression is associated with tumor aggressiveness, chemotherapy resistance, tumor progression, and poor survival prognosis ( Yu et al, 2013 ; Gao et al, 2017 ; Vallejo et al, 2017 ; Xu et al, 2017 ; Sobolev et al, 2022 ). It has been shown that FOSL1 can promote the development and invasion of colorectal cancer through the Smurf1-mediated FBXL2/Wnt/β-catenin axis and the migration, invasion, and proliferation of breast, head, and neck squamous cell carcinoma, pancreatic cancer, bladder cancer, and prostate cancer ( Elangovan et al, 2018 ; Luo et al, 2018 ; Cui et al, 2020 ; Dai et al, 2021 ; Hyakusoku et al, 2021 ; Liu et al, 2021 ). In addition, FOSL1 also mediates the dephosphorylation of proliferation and apoptosis bridging protein 15 (PEA15) by upregulating dual-specificity phosphatase 7 (DUSP7), which increases drug resistance in breast cancer ( Li et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…FOS-like antigen 1 (FOSL1) has an important prognostic value in different tumors, as its overexpression correlates with tumors progression or worse patient survival [ 10 ]. Furthermore, the functions of FOSL1 in promoting epithelial-mesenchymal transition, resulting in cancer spread and metastasis, were reported in various malignant tumors, such as breast, colorectal, prostatic, lung, nasopharyngeal, thyroid, pancreatic, gastric carcinomas, and malignant melanoma [ 11 ].…”
Section: Introductionmentioning
confidence: 99%